ACROSS THE CITY - Anna Madoeuf (Bollettino della Società Geografica Italiana)
In Egypt, the mawlids are at the same time an occasion of feast and pilgrimage, a unique term that identify composite and multiple situations. In Cairo, these celebrations include both provincials and Cairotes, devout persons and onlookers, and they produce infinite opportunities for the blending of different social classes. Urban space is transfigured, crowded, multiplied, overexposed, saturated and it reveals original possibilities of interpretation. Common and private spaces are scrambled into a series of places that assume innovative functions. In this multiplied landscape, sketches and realisations reveal the practices of the participants that share the same places, in a subtle game of proximity and distance, vicinity and separation. In these events, different possible readings of the nature of public space are possible, especially with reference to the practice of a crowded common space. Yet, the mawlids are not at the core of the city’s life, neither symbolically nor politically. Instead, they may be read for their multiple social, spatial, temporal and symbolic marginality.